2015
DOI: 10.1667/rr13855.1
|View full text |Cite
|
Sign up to set email alerts
|

Induction and Repair of DNA DSB as Revealed by H2AX Phosphorylation Foci in Human Fibroblasts Exposed to Low- and High-LET Radiation: Relationship with Early and Delayed Reproductive Cell Death

Abstract: The spatial distribution of radiation-induced DNA breaks within the cell nucleus depends on radiation quality in terms of energy deposition pattern. It is generally assumed that the higher the radiation linear energy transfer (LET), the greater the DNA damage complexity. Using a combined experimental and theoretical approach, we examined the phosphorylation-dephosphorylation kinetics of radiation-induced γ-H2AX foci, size distribution and 3D focus morphology, and the relationship between DNA damage and cellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
77
1
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 59 publications
6
77
1
3
Order By: Relevance
“…The existence of more than one DSB under a focus can be an issue for underestimation and the correct assignment of focus size can improve this situation but up to a point. The yields we found for low-LET (Figure 2) are compatible with previous findings of 10-20 DSB foci/Gy/cell [37,42,43] and the same stands also for a-particles [35,44,45] and Ar ions [46], although in the specific study 40 Ar ions of a much lower LET (125 keV/lm) were used. Previous studies using cold lysis PFGE protocols in order to minimize conversion of heat-labile sites to DSBs suggest relatively increased numbers of $25 DSBs/Gy/cell for normal human skin fibroblasts (GM5758) for low-LET radiations [47].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The existence of more than one DSB under a focus can be an issue for underestimation and the correct assignment of focus size can improve this situation but up to a point. The yields we found for low-LET (Figure 2) are compatible with previous findings of 10-20 DSB foci/Gy/cell [37,42,43] and the same stands also for a-particles [35,44,45] and Ar ions [46], although in the specific study 40 Ar ions of a much lower LET (125 keV/lm) were used. Previous studies using cold lysis PFGE protocols in order to minimize conversion of heat-labile sites to DSBs suggest relatively increased numbers of $25 DSBs/Gy/cell for normal human skin fibroblasts (GM5758) for low-LET radiations [47].…”
Section: Discussionsupporting
confidence: 92%
“…Therefore in the case of a c-H2AX focus which can spread to a chromosome region up to 10-20 Mbp [19], one can expect roughly $0.2-0.4 DSB and 2-4 TSB per focus (low-LET and 1 Gy). DSB clusters are expected for higher doses or high-LET particles where there is a non-homogenous density of breaks along the particle track and one expects even 8 DSBs per focus for a-particles based also on PARTRAC simulations [35]. The electron energies studied cover the low-medium LET range (1-20 keV/lm), so the results can be used to explain some of the characteristics associated with the transition from low-to high-LET radiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data showed that exposure to alpha particles in vitro produced induced DNA and chromosomal damage, consequently decreasing cell survival rate (Antonelli et al, 2015;Sumption et al, 2015). In our study, cell survival rate was also reduced in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the efficiency of the DNA DSBs repair induced by radiation of different quality based on the γH2AX foci formation and elimination kinetics was also shown in [4]. However in this study only a qualitative analysis of the complexity of the induced lesions was performed.…”
Section: Introductionmentioning
confidence: 96%